2019
DOI: 10.5296/ifb.v6i1.14311
|View full text |Cite
|
Sign up to set email alerts
|

ODA and Provincial Economic Growth in Vietnam

Abstract: The focal point of this paper is focused on assessing the causal relationship between ODA and economic growth in the localities of Vietnam. This research uses panel data of ODA and GDP from 63 provinces of Vietnam by using Granger Causality test. The results showed that ODA has a causal effect on economic growth (GDP) and vice versa, economic growth decides to attract ODA in provinces in Vietnam. This result complements studies on the causal relationship between ODA and economic growth using new empirical evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In addition, a few studies focused on the economic effectiveness of aid at sub‐national levels. Duc and Lan (2019) used Granger Causality test, panel data of aid, and the GDPs of 63 Vietnamese provinces over the period 2005–2015 to explore their relationship and determine that aid has a causal effect on economic growth. Civelli et al (2018) utilised spatial panel vector‐autoregressive model estimation, nightlight data, and geo‐located AidData to explore the impact of aid on the regional growth in Uganda and determine that aid has a statistically significant positive and persistent effect on nightlight expansion, an indicator reflecting regional development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, a few studies focused on the economic effectiveness of aid at sub‐national levels. Duc and Lan (2019) used Granger Causality test, panel data of aid, and the GDPs of 63 Vietnamese provinces over the period 2005–2015 to explore their relationship and determine that aid has a causal effect on economic growth. Civelli et al (2018) utilised spatial panel vector‐autoregressive model estimation, nightlight data, and geo‐located AidData to explore the impact of aid on the regional growth in Uganda and determine that aid has a statistically significant positive and persistent effect on nightlight expansion, an indicator reflecting regional development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, from 2008 up to 2015, the relation diagram between these two factors has not been following any certain principle, even in inverse proportion to each other. The analysis of Pearson's correlation coefficients between ODA andGDP growth showed that foreign aid and economic growth in Vietnam has a negative relationship Duc & Lan (2019). complemented studies on the causal relationship between ODA and economic growth using new empirical evidence through case studies in the provinces of Vietnam.…”
mentioning
confidence: 99%